The Effects of Relative Performance Information and Work-Training Tradeoff on Employees’ Skill Development: An Experimental Investigation - Arnold, Markus C.; Shi, Bei; Tafkov, Ivo D.; Voermans, Elien (The Accounting Review, 2025)
ABSTRACT Employees’ skill development is key to organizations’ competitiveness in a global, knowledge-based economy. Prior research in accounting, however, has mainly focused on motivating the provision of transitory effort. This study investigates how relative performance information (RPI) as a management control influences employees’ willingness to engage in skill development and whether the effect of RPI depends on whether employees face a tradeoff between training and current work performance. We predict and find that RPI increases the likelihood of taking training when a work-training tradeoff is absent but decreases it when a work-training tradeoff is present. We also predict and find RPI increases employee performance when a work-training tradeoff is absent and the effect is less positive (and directionally negative) when a work-training tradeoff is present. Our paper is an important first step in investigating how management controls interfere with employees’ investment in skill development and its tradeoff with transitory effort provision. Data Availability: Data are available upon request. JEL Classifications: M21; M41; M52.